Tactical analysis of top ranked players and its implications to educating players and coaches in table tennis - Grycan, J. (Proceedings Book of The 16th ITTF Sports Science Congress Budapest (HUN), April 19th - 20th, 2019, 2020)
Top ranked players 2016-19 representing main type-styles of play were selected: topspin and fast attack (ex. Ma Long, Fan Zhendong, Harimoto, Lin Gaoyuan, Boll, Ding Ning), pen-hold topspin and fast attack (ex. Xu Xin, Wang Hao, Zheng Peifeng), fast and topspin attack (ex. Falk, Ito), chopping defence (ex. Joo Sehyuk, Filus, Ma Te, Li Qian, Wu Yang), `kombi-attack` (ex. He Zhuojia, Fukuhara, Ni Xialian, Zhou Xintong). Over 30 matches among and against top ranked players were selected to perform statistical analysis. The method of game analysis of professor Wu Huanqun, modified by the author, enabled statistical results in main fragments of the game: service-counterattack, return-counterattack, push-counterattack, attackcounterattack, block-counterattack, chop-counterattack, attack-against-chopping. The implications for building training systems in table tennis, especially for FUNdamental 1&2 stages children (ex. talent identification and long-term training) and Level 2 coaching education programs will be presented.